Peran Kepemimpinan Kepala Smk Dalam Mengembangkan Teaching Factory Untuk Meningkatkan Kompetensi Siswa - Hindarto Hindarto; Jasno Jasno; Rulli Widiantoro; Bambang Sumardjoko; Sri Lahir (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE ROLE OF VOCATIONAL SCHOOL PRINCIPAL LEADERSHIP IN DEVELOPING A TEACHING FACTORY TO IMPROVE STUDENT COMPETENCE Vocational High Schools (SMK) are required to produce graduates relevant to the needs of the Business and Industrial World (DUDI). One key strategy for bridging the competency gap is through the implementation of Teaching Factories (TeFa). This study analyzes the leadership role of vocational high school principals in developing Teaching Factories (TeFa) through the integration of Total Quality Management (TQM) and a collaborative culture to improve student competency. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation studies. The results indicate that principal leadership is a key driver through four strategic pillars: (1) aligning the vision with industry needs, (2) implementing quality management in the production process, (3) strengthening a collaborative culture among teachers, and (4) optimizing the budget for industry-standard facilities. This synergy has been proven to significantly improve students' hard and soft skills. The success of TeFa depends heavily on the principal's managerial capacity in transforming the school's organizational culture into an industrial work culture. This study recommends strengthening the entrepreneurial spirit of principals to support the sustainability of vocational education.